Multivariate quality control studies applied to Ca(II) and Mg(II) determination by a portable method - Marzo, J. B.; Medina-Hernandez, M. J.; Sagrado, S.; Bonet, E.; Gimenes, R. (Wiley-Blackwell, 1998)
A portable or field test method for simultaneous spectrophotometric determination of calcium and magnesium in water using multivariate partial least squares (PLS) calibration methods is proposed. The method is based on the reaction between the analytes and methylthymol blue at pH 11. The spectral information was used as the X-block, and the Ca(II) and Mg(II) concentrations obtained by a reference technique (ICP-AES) were used as the Y-block. Two series of analyses were performed, with a month's difference between them. The first series was used as the calibration set and the second one as the validation set. Multivariate statistical process control (MSPC) techniques, based on statistics from principal component models, were used to study the features and evolution with time of the spectral signals. Signal standardization was used to correct the deviations between series. Method validation was performed by comparing the predictions of the PLS model with the reference Ca(II) and Mg(II) concentrations determined by ICP-AES using the joint interval test for the slope and intercept of the regression line with errors in both axes. (C) 1998 John Wiley & Sons, Ltd.
Keywords: partial least squares (PLS) regression; multivariate statistical process control (MSPC); signal standardization; calcium and magnesium multicomponent analysis; analysis of water